2020
DOI: 10.1111/medu.14381
|View full text |Cite
|
Sign up to set email alerts
|

A review to characterise and map the growth mindset theory in health professions education

Abstract: Introduction Growth mindset is a motivation theory proposed by Carol Dweck that posits our beliefs about intelligence, and the ability to change mindsets can have impacts on how we approach challenges, respond to criticism challenges and orient our goals. This study characterised articles on growth mindset theory in health professions education to: summarise the aspects of growth mindset being researched, describe the discussed benefits of growth mindset theory and outline strategies discussed that may promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 55 publications
0
52
0
Order By: Relevance
“…In this issue of Medical Education , Wolcott et al 2 reviewed the literature on health professions education to map and characterise Dweck's research. The authors recommend further investigation and application of this groundbreaking work.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Medical Education , Wolcott et al 2 reviewed the literature on health professions education to map and characterise Dweck's research. The authors recommend further investigation and application of this groundbreaking work.…”
mentioning
confidence: 99%
“…People maintaining growth mindsets take a ‘mastery approach’—they seek challenge and experience mistakes as necessary for improvement 1 . Wolcott et al 2 found that the literature focuses on individual learner mindsets and that less is known about educator and organizational mindsets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational culture around coaching A growth mindset culture can be nurtured with specific strategies targeted at the trainee, the supervisor, and the organization. For example, having an explicit session on growth mindset during resident orientation has been shown to facilitate the coaching feedback process [33]. Supervisors need to provide the psychological safety to ensure that learners can be open and vulnerable about their challenges and weaknesses and seek feedback for growth [34].…”
Section: Mindset Of the Traineementioning
confidence: 99%
“…Clinical faculty are uniquely poised to role model this behavior by discussing their own weaknesses and uncertainties, and by being overtly receptive to feedback themselves [35]. At an organizational level, the promotion of a safe and just culture that promotes feedback at all levels is essential [33]. In addition, providing the physical space to encourage and support direct observation, and developing a culture that nurtures essential trusting relationships between trainees and supervisors, is paramount to successful coaching.…”
Section: Mindset Of the Traineementioning
confidence: 99%